AQUATIC BEETLE ASSEMBLAGES RESPONSE TO DROUGHT IN SMALL WOODLAND STREAMS - Koszałka, Jacek (Polish Journal of Natural Sciences, 2023)
The effect of an unstable hydrological regime on aquatic beetle (Coleoptera) assemblages in intermittent streams (with periodic summer droughts in some segments) was investigated in two successive years with differing climatic conditions. Samples were taken after complete flow resumption in October in each of four unnamed streams flowing into and out of Lake Łękuk Wielki (northeastern Poland). Nine taxa representing five families of aquatic beetles were identified. Seasonal changes in the density and biomass of aquatic beetles were similar in both years of the study. Maximum values of those parameters were noted in the fall followed by strong, distinct decreases in January. The null hypothesis that there was no difference between dry and wet years for taxon richness, mean biomass, and mean density was tested. No significant differences for these attributes were noted, except biomass at one station. Significant differences (ANOSIM, p < 0.05) were determined in beetle assemblages between wet and dry years.